2018
DOI: 10.1002/jia2.25083
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the use of cardiovascular interventions in HIV‐positive persons; the D:A:D Study

Abstract: IntroductionThere is paucity of data related to potential gender differences in the use of interventions to prevent and treat cardiovascular disease (CVD) among HIV‐positive individuals. We investigated whether such differences exist in the observational D:A:D cohort study.MethodsParticipants were followed from study enrolment until the earliest of death, six months after last visit or February 1, 2015. Initiation of CVD interventions [lipid‐lowering drugs (LLDs), angiotensin‐converting enzyme inhibitors (ACEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…PLWH with these risk factors should be monitored and counseled on lifestyle changes. Being female and black ethnicity were associated with a lower risk of dyslipidemia, consistent with results from other studies [49,50]. Compared with ART-naive individuals, ART-experienced PLWH had a lower risk of dyslipidemia.…”
Section: Discussionsupporting
confidence: 90%
“…PLWH with these risk factors should be monitored and counseled on lifestyle changes. Being female and black ethnicity were associated with a lower risk of dyslipidemia, consistent with results from other studies [49,50]. Compared with ART-naive individuals, ART-experienced PLWH had a lower risk of dyslipidemia.…”
Section: Discussionsupporting
confidence: 90%
“…By contrast, the international D:A:D cohort of > 49 000 PLWH found many CVD risk factors to be more common in MLWH, including hypertension (7% vs. 10.8%) and diabetes (1.7% vs. 2.7%) [22].…”
Section: Resultsmentioning
confidence: 99%
“…We also found that women with HIV were more prone to have CVE than their HIV-negative pairs, while this difference was not observed with men, even though the absolute IR in CoRIS was lower in women. Different causes have been implicated for this gender-dependent increased risk, such as a higher prevalence of atherosclerotic plaques in women with HIV [29], less monitoring of interventions to prevent cardiovascular risk in women with HIV [30], and increased immune activation associated with female gender [31]. The relevance of prevention is emphasized by the fact that mortality was twice-as-high in PLWH with vascular events compared to those without events.…”
Section: Discussionmentioning
confidence: 99%